Analytical Methods Validation of Retinoic Acid and Hydroquinone Using Ultra High Performance Liquid Chromatography in Medicinal Cream - Linda Mazroatul; Annisa Ananda Ulya; Supandi Supandi; Umar Mansur (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2019)
Hydroquinone and retinoic acid have been widely used as whitening agents in cosmetic creams and have a negative impact if used without a medical prescription. In this study, development of analytical method of retinoic acid (REA) and hydroquinone (HYQ) were carried out using Ultra High Performance Liquid Chromatography (UHPLC) with a PDA detector, Phenomenex Luna® ODS / C18 column (150 mmx4.6 mm), methanol-acetic acid 0.1% (85:15) as mobile phase, flow rate of 1.0 mL/min and detected at 295 nm for HYQ and 341 nm for REA. The result of the validation method showed a retention time of HYQ at 1.55 minutes and REA at 3.73 minutes. Validation parameters performed are selectivity, range, linearity, LOD, LOQ, accuracy, and precision. Linear detector response in the concentration range of 75-250 ppm with a calibration curve equation. The calibration curve equation for HYQ is y = 0.4607x + 1.9014 (r = 0.999), mean while REA is y = 2.3138x + 21.0429 (r = 0.999). LOD and LOQ values of HYQ are 1.615 ppm; 13.98 ppm respectively and REA 1.02 ppm and 3.11 ppm, respectively. The precision (% RSD) ≤ ± 2% and accuracy (% recovery) in the range of 99.0% - 100.6%. This method is valid to be used to analyze HYQ and REA in commercial cosmetic cream samples.